2015
DOI: 10.1039/c5ra17351e
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Cu/OMS-2 as an efficient catalyst for the synthesis of tetrasubstituted 1,4-enediones and 4H-pyrido[1,2-a]-pyrimidin-4-ones

Abstract: An efficient Cu/OMS-2-catalyzed oxidative heterogeneous protocol has been developed for the synthesis of tetrasubstituted unsymmetrical 1,4-enediones and 4H-pyrido[1,2-a]-pyrimidin-4-ones from 1,4-enediones and amines or 2-aminopyridines. The present catalytic system employs air as the termial oxidant and tolerates a broad range of substrates using low loading copper (1.3 wt%). The Cu/OMS-2 was characterized by various methods, including XRD, XPS, BET as well as TEM/SEM, and the results of H2-TPR shows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 88 publications
2
8
0
Order By: Relevance
“…It was apparent that the CuFeO x /OMS-2 has nanorodshaped morphology, with a diameter of approximately 13 nm and length from 300 to 500 nm. is result is consistent with that in the study of Zhang et al [18] reported on related OMS-2 materials.…”
Section: Materials Synthesis and Characterizationsupporting
confidence: 93%
See 1 more Smart Citation
“…It was apparent that the CuFeO x /OMS-2 has nanorodshaped morphology, with a diameter of approximately 13 nm and length from 300 to 500 nm. is result is consistent with that in the study of Zhang et al [18] reported on related OMS-2 materials.…”
Section: Materials Synthesis and Characterizationsupporting
confidence: 93%
“…e XRD patterns of the catalysts are displayed in Figure 4. It has been observed that the diffraction peaks at 2θ of 12.6°, 17.9°, 28.7°, 37.5°, 41.9°, 49.9°, and 60.1°directly contributed to the crystalline phase of cryptomelane (KMn 8 O 16 ), proving that the nanorod OMS-2 material had a cryptomelane-type structure [19], corresponding to the XRD patterns of OMS-2 material in some works [18,19]. Although appearing at relatively low intensity, the diffraction peaks at 2θ of 32.6°, 35.5°, and 38.8°in XRD patterns of Cucontaining catalysts could be attributed to its low crystalline phase of copper oxide [11].…”
Section: Materials Synthesis and Characterizationmentioning
confidence: 70%
“…The CuMnO x /OMS-2 exhibits nanorod-shaped morphologies, with diameters of about 13 nm and lengths of 300-500 nm ( Figure 1A). This observation consists with the literatures result about the related OMS-2 materials [21]. Especially, the Figure 1B (zoomed up from Fig.1A at the red square position) shows the light line on the OMS-2 nanorod surface.…”
Section: Electron Microscopysupporting
confidence: 89%
“…2 indicates the diffraction peaks at 2θ of 12.6 o , 17.9 o , 28.7 o , 37.5 o , 41.9 o , 49.9 o , and 60.1 o which are attributed to the crystalline phase of cryptomelane (KMn 8 O 16 ), indicating that the nanorod OMS-2 material has a cryptomelane-type structure [22]. It consists with the XRD pattern of OMS-2 material in the literatures [21,22]. However, for XRD pattern of CuO/OMS-2 catalyst, the diffraction peaks at 2θ of 32.6 o , 35.5 o , 38.8 o are attributed to the crystalline phase of copper oxide [17].…”
Section: Xrd Ft-ir and Surface Area Of Catalystsmentioning
confidence: 69%
“…As a part of our continuing efforts on heterogeneous synthesis, we have developed several systems for the heterocycles synthesis by employing a series of manganese oxide-supported copper (Cu/OMS-2) as catalysts and air as green oxidant. [11][12][13] In terms of catalytic mechanism, we envisaged the catalytic system combines two redox couples: supported The filtrate was removed under reduced pressure to get the crude product, which was further purified by silica gel chromatography (petroleum/ethyl acetate = 40/1-50/1 as eluent) to yield corresponding product. The identity and purity of the products were confirmed by 1 H, 13 C NMR spectroscopic and HRMS analysis.…”
Section: Introductionmentioning
confidence: 99%